Psychological Characteristics of Anxiety in Primiparous and Multiparous Pregnant Women - Firyan, Ara; Davtyan, Narine (ՀՀ ԳԱԱ)
Improving the health of citizens is a priority for any state. And, accordingly, women’s reproductive health and maternity deserve great attention, because both the physical and mental health of pregnant women is a key factor in the health of the nation. Pregnancy is a difficult stage in a woman’s life, often accompanied by increasing anxiety. Numerous studies prove the linkage between the mental health of the future child and the mother’s psychological and emotional problems during pregnancy. Perinatal psychology, a relatively new direction in psychological science, deals with these issues. Улучшение здоровья граждан является приоритетом для любого государства. И, соответственно, репродуктивное здоровье женщин и материнство заслуживают большого внимания, потому что как физическое, так и психическое здоровье беременных женщин является ключевым фактором здоровья нации. Беременность – сложный этап в жизни женщины, часто сопровождающийся нарастающей тревожностью. Многочисленные исследования доказывают связь психического здоровья будущего ребенка с психологическими и эмоциональными проблемами во время беременности матери. Данными вопросами занимается перинатальная психология – относительно новое направление в психологической науке. Քաղաքացիների առողջության բարելավումը առաջնահերթ է ցանկացած պետության համար։ Եվ համապատասխանաբար կանանց վերարտադրողական առողջությունը և մայրությունը մեծ ուշադրության են արժանի, քանի որ հղի կանանց թե՛ ֆիզիկական և թե՛ հոգեկան առողջությունը ազգի առողջության գրավականն է։ Հղիությունը կանանց կյանքում բարդ փուլ է, որը հաճախ ընթանում է տագնապայնության բարձրացումով։
Keywords: Social and Humanitarian Sciences